2018
DOI: 10.1016/j.ejphar.2017.11.044
|View full text |Cite
|
Sign up to set email alerts
|

Inhalation anaesthetic isoflurane inhibits the muscarinic cation current and carbachol-induced gastrointestinal smooth muscle contractions

Abstract: Gastrointestinal tract motility may be demoted significantly after surgery operations at least in part due to anaesthetic agents, but there is no comprehensive explanation of the molecular mechanism(s) of such adverse effects. Anesthetics are known to interact with various receptors and ion channels including several subtypes of transient receptor potential (TRP) channels. Two members of the canonical subfamily of TRP channels (TRPC), TRPC4 and TRPC6 are Ca2+-permeable cation channels involved in visceral smoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 34 publications
1
11
0
6
Order By: Relevance
“…Overall, ketamine induced inhibition of mI CAT is highly reminiscent of the effects of isoflurane (Dryn et al, 2018). To our knowledge, our experiments provide first indication that G-proteins can be inhibited by ketamine, but obviously much further work is required to clarify the underlying mechanism.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Overall, ketamine induced inhibition of mI CAT is highly reminiscent of the effects of isoflurane (Dryn et al, 2018). To our knowledge, our experiments provide first indication that G-proteins can be inhibited by ketamine, but obviously much further work is required to clarify the underlying mechanism.…”
Section: Discussionmentioning
confidence: 72%
“…The ileum longitudinal smooth muscle (SM) layer was rapidly removed by carefully peeling the SM in the longitudinal direction and placed into a normal physiological salt solution (PSS) containing (in mM): NaCl 120, glucose 12, HEPES 10, KCl 6, CaCl 2 2.5, MgCl 2 1.2, pH 7.4 (adjusted with NaOH). SM cells were isolated by enzymatic digestion using (in mg/ml) 1 collagenase type 1A, 1 soybean trypsin inhibitor II-S, 1.5 bovine serum albumin in divalent cation-free PSS following tissue incubated for 18 min at 36.5°C, as described in more detail elsewhere (Dryn et al, 2018).…”
Section: Cells Isolationmentioning
confidence: 99%
See 1 more Smart Citation
“…Tsvilovskyy et al concluded that TRPC4 and TRPC6 channel activation are critical for stimulating the muscarinic cation current (mICAT) in intestinal smooth muscle [ 255 , 256 ], indicating that the mICAT may consist of TRPC4 and TRPC6 and that their activation may be important for accelerating intestinal motility. It has been reported that the inhibitory effect of anesthetic agents, such as isoflurane, decreasing gastrointestinal tract motility is mediated by inhibiting the G-protein signaling that is important for stimulation of mICAT formed by TRPC4 and TRPC6 channels [ 257 ]. However, the reports on the function of TRPCs in the gastrointestinal tract are scarce and new investigations are needed to better understand their contribution to regulating gut function.…”
Section: Physiological and Pathological Functions Of Trpcs Revealementioning
confidence: 99%
“…Activated receptors result in the contraction of gastrointestinal smooth muscles via Ca 2+ influx. There are reports that the activated muscarinic receptor opens non-selective cation channels which depolarizes the membrane in guinea-pig jejunal smooth muscles [ 33 ], that TRPC4 and TRPC6 are involved in visceral smooth muscle contractility induced by ACh [ 10 , 15 ], and that TRPC3/C6/C7 are involved in Ca 2+ currents mediated by muscarinic receptor [ 19 ]. In the stressed ileum, in contrast, the second half of the EFS-induced contraction was suppressed by 80% under atropine-treated conditions.…”
Section: Discussionmentioning
confidence: 99%